Quality Analysis of E-Learning Website (Elena) Using Webqual 4.0 Method and Importance Performance Analysis (IPA) - Pamungkas, Dimas Hardi; Subhan, Subhan (Journal of Advances in Information Systems and Technology, 2023)
E-learning website is one of the important elements in education which has a role as an online learning medium. It is important to measure the quality of e-learning website services to maintain the ongoing use of the e-learning website. This research was conducted for evaluation in order to measure and improve the quality of e-learning website services at Semarang State University (Elena) using the Webqual 4.0 method and Importance Performance analysis (IPA) which has a focus on four variables, which that is; usability, information quality, service interaction quality, and overall, as well as to determine the value of user perceptions and expectations of the services that have been provided. Based on the results of the calculations that have been carried out, the Customer Sutisfaction Index (CSI) value is 76.4%, meaning that the respondents stated that they were satisfied with the performance of Elena's e-learning website. The results of calculating the average value of the gap (Gap) on Elena's e-learning website still show a significant negative value of -0.64, these results indicate that the performance level of Elena's e-learning website still does not meet user expectations. The results of the analysis of the IPA quadrants obtained 2 attributes which were included in quadrant I, 10 attributes entered in quadrant II, 7 attributes entered in quadrant III, and 4 quadrants entered in quadrant IV. This research is expected to provide positive input for website managers to be able to improve the quality of services provided to users in the future.